In Vivo Kinetics and Biotransformation of Aflatoxin B1 in Dairy Cows Based on the Establishment of a Reliable UHPLC-MS/MS Method - Guo, Wenbo; Fan, Zhichen; Fan, Kai; Meng, Jiajia; Nie, Dongxia; Tangni, Emmanuel K.; Li, Zenghe; Zhao, Zhihui; Han, Zheng (Frontiers in Chemistry, 2021)
The in vivo kinetics of aflatoxin B1 (AFB1) and its carry-over as aflatoxin M1 (AFM1) in milk and the toxin loads in the tissue of dairy cows were assessed via a repetitive feeding trial of an AFB1-contaminated diet of 4 μg kg-1 b.w. for 13 days. This was followed by a clearance period and ended with a single dose trial of an AFB1-contaminated diet of 40 μg kg-1 b.w.. An ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) method was developed and successfully validated by the determination of linearity(R2≥0.990), sensitivity (lower limit of quantification, 0.1–0.2 ng mL-1), recovery (79.5–111.2%), and precision (RSD≤14.7%) in plasma, milk and various tissues. The biotransformation of AFB1 to AFM1 occurred within 48 h and the clearance period of AFM1 in milk was no more than 2 days. The results of toxicokinetics indicated that AFB1 reached a maximum concentration of 3.8±0.9 ng mL−1 within 35.0±10.2 min and was slowly eliminated from plasma with a half-life time (T1/2) of 931.1±30.8 min. Meanwhile, AFM1 reached a plateau in plasma (0.5±0.1 ng mL-1) at 4 h after the ingestion. AFB1 was found in the heart, spleen, lungs, and kidneys with concentrations of 1.6±0.3, 4.1±1.2, 3.3±0.9 and 5.6±1.4 μg kg-1, respectively. AFM1 was found only in the spleen and kidneys at concentrations of 0.7±0.2 and 0.8±0.1 μg kg-1, respectively. In conclusion, the carry-over and toxicokinetics of AFB1 in dairy cows were determined using the developed UHPLC-MS/MS method and several toxicological findings of AFB1 from feed to milk and tissues were clearly demonstrated, which could be helpful in assessing the health risks to consumers.